(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
Oral dissolving drug delivery system offers a solution for those patients having difficulty in swallowing tablets/capsules. The primary objective of the present research work was to optimize oral thin film (OTF) formulation of phenylephrineÂ HCl, a water soluble drug with three loading concentrations: High, medium and low and also to evaluate their effect on theÂ final product attributes.The OTF was prepared by solvent casting method. All the formulations were evaluated for film formingÂ properties, appearance, thickness, folding endurance, tensile strength, percent moisture absorption, surface morphology,Â in vitro and in vivo disintegration. Formulations containing low and medium loading concentration gave acceptable results whileÂ formulation with higher loading concentration resulting poor film forming properties. Hence, another objective of the presentÂ study was to investigate the effect of antiâ€tacking agent namely magnesium aluminum silicate (MAS), microcrystalline celluloseÂ and colloidal silicon dioxide (CSD) by applying 23 full factorial design on improving the film properties of high concentrationÂ phenylephrine HCl. Formulation containing microcystalline cellulose and CSD at low level and MAS at high level was foundÂ to be suitable for film formation with desirable physicochemical properties, faster disintegration and optimum in vitro release. Key words: Antiâ€tacking agents, effect of variables, loading concentration, water soluble drugs